MANIPULATING OIL SEED BIOCHEMISTRY TO ENHANCE THE PRODUCTION OF ACETYL-TAGS - Kornacki, Catherine (Kansas State University, 2016)
Using vegetable oils directly as an alternative biofuel presents several problems as such oils typically possess poor fuel qualities including high viscosity, low volatility, and poor cold temperature properties. The ornamental shrub Euonymus alatus produces unusual acetyl-1,2-diacyl-sn-glycerols (acetyl-TAGs) that have an acetyl group in the sn-3 position instead of a long chain fatty acid. The presence of this sn-3 acetyl-group give acetyl-TAGs properties desirable for biofuels, such as reduced viscosity, comparted to the normal long chain triacyglycerols found in most vegetable oils. Acetyl-TAGs are synthesized by the Euonymus alatus diacylglycerol acetyltransferase (EaDAcT) and Euonymus fortunei diacylglycerol acetyltransferase (EfDAcT) enzymes. Both enzymes catalyze the transfer of an acetyl group from acetyl-CoA to diaclglycerol (DAG) to produce acetyl-TAGs. Previous work demonstrated that expression of EaDAcT combined with the suppression of a diacylglycerol aceyltransferase (DGAT1) in Camelina sativa led to seeds with 85 mol % acetyl-TAGs. Increasing acetyl-TAG levels further was explored using two strategies. Over expression of citrate lyase to increase the pool of acetyl-CoA to be used as a substrate for the acetyltransferase enzymes failed to increased levels of acetyl-TAGs. A second approach involved expressing EfDAcT in Camelina sativa. EfDAcT has demonstrated higher activity in vitro and in vivo and its expression in yeast leads to approximately 50 % higher levels of acetyl-TAGs compared to EaDAcT. The expression of EfDAcT coupled with the suppression of DGAT1 in Camelina sativa resulted in 90 mol % acetyl-TAGs in the transgenic seeds. Levels of EfDAcT protein analyzed in developing transgenic Camelina sativa seeds across a 40 day time period were highest at 15 and 20 days after flowering. Following these time points acetyl-TAG accumulation increased rapidly, coinciding with the higher enzyme expression levels. The optimization of additional promoters to ensure expression of EfDAcT in the last half of seed development could represent another way to further increase acetyl-TAGs in the future.
Keywords: Camelina sativa; Acetyl-TAGs; Metabolic engineering